Urban maps instruments of narrative and interpretation in the city - Brook, Richard (Routledge, Taylor & Francis Group, 2016)
1. Introduction -- 2. Brand, image and identity -- 3. Networks -- 4. Films -- 5. Marks -- 6. Object -- 7. Conclusion.
Keywords: Städtebau; Medien; Stadtplanung; Stadtforschung; Stadt; Cities and towns / Maps; Urbanization / Maps; Urban geography